PEREMPUAN SEBAGAI OBJEK MALE GAZE PEMBACA: TELAAH KRITIS KARYA SASTRA FEMINIS PEREMPUAN INDONESIA - Febrianto, Anggit; Udasmoro, Wening (Adabiyyāt: Jurnal Bahasa dan Sastra, 2024)
Since the fall of Suharto in May 1998, women's involvement in literature has increased rapidly, causing a rush of feminist themes and content in literary works in this period. However, the literary works of women writers, even female feminists, are still unable to escape the tendency to objectify women. This research will show that in the works of female feminist writers, female characters are still displayed as objects of the reader’s male gaze. Four novels will be studied, namely Perempuan Berkalung Sorban and Geni Jora by Abidah El Khalieqy, and Tabula Rasa and Gadis Kretek by Ratih Kumala. This study is descriptive qualitative. Data collection techniques were carried out using the literature study method, namely by reading carefully and thoroughly the four material object novels. Collected data will be analyzed using the Male Gaze Theory by Laura Mulvey. According to the Male Gaze Theory, women are constantly looked at, watched, and displayed, with a certain appearance that has a strong visual and sexual influence so that they are referred to as to-be-looked-at-ness. The results of this study show that in the four novels, there are two repeated patterns, that consistently place women as objects of the reader’s male gaze, namely (1) the exposure of women's intimate organs in an erotic context and (2) beautiful and detailed descriptions of women's faces and bodies.